Implementasi Sistem Ujian Online Berbasis Android: Studi Kasus Smp Yamad Bekasi - Andi Prastomo (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2020)
Android is a Linux-based operating system used for mobile devices such as smartphones and tablets. In education sector, the use of smartphones for online-based exams can make the examination process easier and faster. In addition to being practical in terms of making questions and checking answers, using smartphones can also reduce expenses such as reducing the use of paper and stationery. Junior High School Yamad Bekasi has not implemented an online test system with an android-based smartphone device. Based on this, the researchers conduct research with the theme of Implementing the Android-Based Online Examination System using the Applied Research method. The application design uses the Waterfall method with Stages of Analysis with the Requirement elicitation method, while the test uses Software Quality Assurance (SQA) method. The results of this study emphasize more on the system requirements analysis stage with the Requirement Elicitation method with the Final Draft Elicitation results in the form of points that must be owned by the system to be developed, while the system testing stage uses the Software Quality Assurance (SQA) method with test scores above the minimum average value of SQA testing of 80.00 so that a system that meets the quality standards well and is feasible to be implemented in assisting the online examination process at SMP Yamad Bekasi can be produced.